Structural, optical and Carrier dynamics of self-assembled InGaN nanocolumns on Si(111). (May 2018) - Kumar, Praveen; Devi, Pooja; Soto Rodriguez, P.E.D.; Jain, Rishabh; Jaggi, Neena; Sinha, R.K.; Kumar, Mahesh
Abstract: We investigated the morphological, structural, optical, electrical and carrier relaxation dynamic changes on the self-assembled grown InGaN nanocolumns (NCs) directly on p -Si(111) substrate at two different substrate temperature, namely 580 °C (A) and 500 °C (B). The emission wavelength of comparably low temperature (LT) grown NCs was red-shifted from 3.2eV to 2.4eV. First observations on the charge carrier dynamics of these directly grown NCs show comparable broad excited state absorption (ESA) for LT gown NCs, which manifest bi-exponential decay due to the radiative defects generated during the coalescence of these NCs. Highlights: Morphological, structural, optical investigations of directly grown InGaN on Si. Fist observation on the charge carrier dynamics of directly grown InGaN/Si NCs. Substrate temperature-induced changes in InGaN NCs.